Origin and function of short-latency inputs to the neural substrates underlying the acoustic startle reflex - Gómez-Nieto, Ricardo; Horta-Júnior, José de Anchieta C.; Castellano, Orlando; Millian-Morell, Lymarie; Rubio, Maria E.; López, Dolores E. (Frontiers in Neuroscience, 2014)
The acoustic startle reflex (ASR) is a survival mechanism of alarm, which rapidly alerts the organism to a sudden loud auditory stimulus. In rats, the primary ASR circuit encompasses three serially connected structures: cochlear root neurons (CRNs), neurons in the caudal pontine reticular nucleus (PnC), and motoneurons in the medulla and spinal cord. It is well-established that both CRNs and PnC neurons receive short-latency auditory inputs to mediate the ASR. Here, we investigated the anatomical origin and functional role of these inputs using a multidisciplinary approach that combines morphological, electrophysiological and behavioral techniques. Anterograde tracer injections into the cochlea suggest that CRNs somata and dendrites receive inputs depending, respectively, on their basal or apical cochlear origin. Confocal colocalization experiments demonstrated that these cochlear inputs are immunopositive for the vesicular glutamate transporter 1 (VGLUT1). Using extracellular recordings in vivo followed by subsequent tracer injections, we investigated the response of PnC neurons after contra-, ipsi-, and bilateral acoustic stimulation and identified the source of their auditory afferents. Our results showed that the binaural firing rate of PnC neurons was higher than the monaural, exhibiting higher spike discharges with contralateral than ipsilateral acoustic stimulations. Our histological analysis confirmed the CRNs as the principal source of short-latency acoustic inputs, and indicated that other areas of the cochlear nucleus complex are not likely to innervate PnC. Behaviorally, we observed a strong reduction of ASR amplitude in monaural earplugged rats that corresponds with the binaural summation process shown in our electrophysiological findings. Our study contributes to understand better the role of neuronal mechanisms in auditory alerting behaviors and provides strong evidence that the CRNs-PnC pathway mediates fast neurotransmission and binaural summation of the ASR.